Abdominal cancer symptoms: Evaluation of the impact of a regional public awareness campaign. (11th August 2021) - Torrance, Nicola; Bright, Chloe J.; Hill, Helen L.; Fergusson, Jennie; Kennedy, Catriona; Mak, Vivian; Gildea, Carolynn; Nordin, Andy; Elliss‐Brookes, Lucy
Abstract: Objective: A regional 'Be Clear on Cancer' (BCoC) campaign developed by Public Health England aimed to promote public awareness of key abdominal cancer symptoms in people aged 50 years and over. Methods: Data were analysed for metrics at different stages in the patient care pathway including public awareness, GP attendance and referrals, to cancer diagnosis. Results: There was significantly higher recognition of the BCoC abdominal campaign in the campaign region compared to the control area (Post Campaign/Control, n  = 401/406; 35% vs. 24%, p  < 0.05). The campaign significantly improved knowledge of 'bloating' as a symptom ( p  = 0.03) compared to pre‐campaign levels. GP attendances for abdominal symptoms increased significantly by 5.8% ( p  = 0. 03), although the actual increase per practice was small (average 16.8 visits per week in 2016 to 17.7 in 2017). Urgent GP referrals for suspected abdominal cancer increased by 7.6%, compared to a non‐significant change (0.05%) in the control area. For specific abdominal cancers, the number diagnosed were similar to or higher than the median in the campaign area but not in the control area in people aged 50 and over: colorectal (additional n  = 61 cancers), pancreatic (additional n  = 102) and stomach cancers (additional n  = 17). Conclusions: This campaign had a modest impact on public awareness of abdominal cancer symptoms, GP attendances and cancers diagnosed.